Optimisation of Biomass Supply Chain Management Using P-Graph Application in FELDA Jengka - Abdul Haleem, Azreennisa (IRC, 2016)
Biomass is one of the alternative sources of energy which has a promising future to complement or replace fossil fuels. However, the main barrier in utilisation of biomass for energy production is the cost associated with biomass supply chain management. Biomass supply chain management involves process of planting, harvesting, storing, transporting and processing. This study is focussed to solve the combinatorial complexity of biomass supply chain in FELDA Jengka, one of the largest oil palm plantations in Malaysia. To address this issue, P-graph optimization software is used to minimise the total cost related to biomass supply chain management and at the same time to reduce the amount of carbon released to the atmosphere along the supply chain.